Своеобразие интертекстуальности в пьесе Т.Стоппарда „Изобретение любви” - Мармазова, Л. (Питання літературознавства, 2009)
Досліджуються такі концептуально значущі літературно-культурологічні інтертекстуальні площини п’єси Тома Стоппарда „Винахід любові”, як антична та вікторіанська. Інтертекстуальність постмодерністської драми розглянуто як один із провідних засобів поширення семантичного потенціалу твору. The article deals with such significant literary and cultural intertextual layers in Tom Stoppard’s The Invention of Love (1997) as ancient and Victorian. Intertextuality in the postmodernist drama is regarded to be one of the leading means that broadens the semantic potential of the play. Plato’s concept of Eros, the ideas, plots and images of the ancient literature, as well as the Victorian attitude towards them disclose a number of themes that constitute the polysemantic nature of T. Stoppard’s play. It is achieved by means of opposing and juxtaposing two „golden ages”, antiquity and the Victorian age, and revealing their similarities and fundamental non-equivalence.